Theory of Intellectual Entrepreneurship: A Foundation Stone of Learning for Self Employed in Industry 4.0 - Muhammad Khalique; Jamal Abdul Nassir Shaari; Khushbakht Hina (Asian Scholars Network (ASNet), 2025)
Indexed by MyCite